Students Satisfaction on Practical Learning in Nursing Laboratory Poltekkes Kemenkes Yogyakarta - Nurun Lasaara (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2018)
The nursing diploma organizes education based on a national curriculum oriented to the development of science and technology as well as professional development and its composition refers to the competence of the nursing profession. Lectures are conducted in theory and practice, both clinical practice, family/community and laboratory practice. Practice in the laboratory is a learning strategy used to teach together psychomotor abilities, cognitive and affective using laboaratorioum means. In the implementation of laboratory practices need to be monitored to monitor the achievement of learning to learners so that can be achieved according to competence. Aim of the study was to determine student satisfaction of learning practice in laboratory of nursing department Health Polytechnic of Ministry of Health in Yogyakarta. The type of this research is quantitative research in the form of satisfaction survey. The population in this research was students of diploma III and IV nursing Health Polytechnic of Ministry of Health in Yogyakarta. The samples in this study were determined in total sampling. In accordance with the inclusion and exclusion criteria, of the 360 ??students, who participated in the study there were 340 students. The measuring instrument used was questionnaire. Data were analyzed using univariate descriptive analysis. From the questionnaires given to the students, from each item of satisfaction indicator that includes reliability, empathy, responsiveness, infrastructure, assurance and communication system of 340 students got an average of more than 80% of respondents answered satisfied to the system of practical practice in the laboratory. The conclusion of the study is that scores derived from satisfaction items that include reliability, empathy, responsiveness, means of infrastructure, certainty and communication systems, average or more than 50% which means that students judge good or satisfied with the learning in the laboratory